Hypertension and hypotension in dental practice: a seven-year retrospective study on third molar extractions - Fernández Franco, Diego Andrés (2024)
Objective: To analyze the prevalence of hypotension and hypertension during third molar extraction at the Faculty of Dentistry between 2012 and 2019, and its relationship with gender and age factors. Materials and methods: Retrospective study, with a review of 1324 clinical records for third molar extraction in the exodontic clinic of the Faculty of Dentistry during 2012-2019. They were divided into three age groups: 20 to 40, 41 to 60 and 61 to 80 years. the parameters that categorize as hypertensive patients presented SBP figures ≥ 140 mmHg and DBP ≥ 90 mmHg. In hypotensive patients, they presented with 40 mmHg in SBP and 20 mmHg in DBP.  Statistics were applied using Minitab 20 software. Results: Of 96 hypertensive patients, 61 were men, whereas, of the 36 hypotensive patients, 19 were women. The age group with the highest prevalence of hypertension, was the 41 to 60 years’ group. Conclusions: In 1324 patients, the prevalence of hypertension and hypotension was 9.9% of these 72.72% with hypertension and 27.27% with hypotension. A direct relationship was established with age, being higher in the 41 to 60 years age group.